"Conjuring up her wholeness": Post-transitional black South African women's poetry and its restorative ethic. (3rd May 2016) - Boswell, Barbara
ABSTRACT: This essay surveys poetry by black South African women published since 2005 as a means of critically engaging the post-transitional literary paradigm. It notes the ways in which black women's poetry has expanded from apartheid and transitionary modes of writing to include four broad categories: gender justice, the body, diasporic identity and re-memorying history. It argues that black women's poetry that inhabits these four literary modes produces a restorative ethic, which seeks to restore and repair histories and subjectivites fractured by colonialism and apartheid.